Cadmium exposure activates the PI3K/AKT signaling pathway through miRNA-21, induces an increase in M1 polarization of macrophages, and leads to fibrosis of pig liver tissue - Wei Cui (Elsevier, 2021)
Cadmium (Cd) is a toxic substance that pollutes the environment with multiple organs. Long-term exposure to Cd can cause fibrosis in the lungs and other organs of animal body. This article explored the effects of subacute Cd exposure on pig liver fibrosis, as well as the polarization of microRNA (miRNA) and M1/M2 macrophages during this process. Based on the establishment of the pig subacute CdCl2 exposure model, we used immunofluorescence staining, Masson staining, qRT-PCR and western blotting to conduct further research. The results showed that Cd exposure can increase the expression of miRNA-21, decrease the expression of TGF-β and SMAD7, increase the expression of PI3K/AKT signaling pathway, cause the M1/M2 imbalance and the increase of M1 polarization. Meantime, it causes the secretion of inflammatory cytokines (TNF-α, IL-1β, and IL-6), and causes an imbalance in the expression of TIMP1, MMP2, and MMP9, which are related to the degree of fibrosis. And the expression of α-SMA, COL1 and COL3 were up-regulated. In the pig, these results indicate that liver fibrosis caused by subacute CdCl2 exposure is induced by the M1 polarization of macrophages through the PI3K/AKT signaling pathway activated by miRNA-21 signaling pathway. These research results not only enrich the theoretical basis and reference value of Cd toxicology research, but also provide new references and new research ideas for comparative medicine.